Tidally Driven Interannual Variation in Extreme Sea Level Frequencies in the Gulf of Maine. Issue 10 (29th September 2020) - Baranes, H. E.; Woodruff, J. D.; Talke, S. A.; Kopp, R. E.; Ray, R. D.; DeConto, R. M.
Abstract: Astronomical variations in tidal magnitude can strongly modulate the severity of coastal flooding on daily, monthly, and interannual timescales. Here we present a new quasi‐nonstationary skew surge joint probability method (qn‐SSJPM) that estimates interannual fluctuations in flood hazard caused by the 18.6‐ and quasi 4.4‐year modulations of tides. We demonstrate that qn‐SSJPM‐derived storm tide frequency estimates are more precise and stable compared with the standard practice of fitting an extreme value distribution to measured storm tides, which is often biased by the largest few events within the observational period. Applying the qn‐SSJPM in the Gulf of Maine, we find significant tidal forcing of winter storm season flood hazard by the 18.6‐year nodal cycle, whereas 4.4‐year modulations and a secular trend in tides are small compared to interannual variation and long‐term trends in sea‐level. The nodal cycle forces decadal oscillations in the 1% annual chance storm tide at an average rate of ±13.5 mm/year in Eastport, ME; ±4.0 mm/year in Portland, ME; and ±5.9 mm/year in Boston, MA. Currently (in 2020), nodal forcing is counteracting the sea‐level rise‐induced increase in flood hazard; however, in 2025, the nodal cycle will reach a minimum and then begin to accelerate flood hazard increase as it moves toward its maximum phase over the subsequent decade. Along the world's meso‐to‐macrotidal coastlines, it is therefore critical to consider both sea‐level rise and tidal nonstationarity in planning for the transition to chronic flooding that will be driven by sea‐level rise in many regions over the next century. Plain Language Summary: Coastal management practices around flood risk often rely on estimates of the percent chance of a particular flood height occurring within a year. For example, U.S. flood insurance requires designating areas with a 100‐year flood recurrence interval (the "100‐year flood zone"). When storms hit regions with large tides, the height and timing of high tide often determine flood severity. Thus, the relationship between flood height and annual frequency can be altered by natural, daily‐to‐decadal cyclical variation in tide heights. Here we present a new method for calculating annually varying flood height‐frequency relationships based on known tidal cycles. Applying the new method in the Gulf of Maine, we find an 18.6‐year‐long tidal cycle (the nodal cycle ) has forced decadal variation in the 1% annual chance flood at a faster rate than the historical average rate of sea‐level rise over the past century. Currently, nodal cycle forcing is counteracting the sea‐level rise‐induced increase in flood hazard; however, in 2025, the nodal cycle will reach a minimum in the Gulf and then begin to accelerate flood hazard as it moves toward its maximum over the subsequent decade. It is therefore critical to consider sea‐level rise and tidal variation in medium‐term flood hazard planning. Key Points: We present a new quasi‐nonstationary joint probability method that estimates tidally driven interannual fluctuations in flood hazard This method provides more precise and stable storm tide frequency estimates than extreme value distributions fit to measured storm tides In the Gulf of Maine, tides force decadal oscillations in the 1% annual chance storm tide at a rate exceeding mean historical sea‐level rise